(untitled) (Research, Society and Development, 2020)
The objective of this article is analyse, inspired on the work of Ludwik Fleck, the construction of knowledge on hand asepsis and its implications for health education. It’s based on a bibliographical review of works published in books, electronic articles, scientific journals, theses, dissertations and manuals that address knowledge related to hand asepsis and Fleck’s thinking. This author’s epistemological approach has importance in the History of Science and in the construction of knowledge based on medicine, since he defends the necessity of the historical-philosophical view of science in the development of a scientific fact. By his contributions, Fleck can be considered a thinker ahead of his time and a forerunner of the historical, cultural and social approach in the construction of science. The gradual acceptance of hand asepsis as a preventive measure against contamination by diseases exemplifies the collective process of building scientific knowledge and reinforces the model proposed by Fleck, since it describes a situation that confirms his conceptions about the stages of production of scientific knowledge.